Reflective portfolios support learning personal growth and competency achievement in postgraduate public health education - Himani Pandya; Wiedaad Slemming; Haroon Saloojee (South African Medical Association, 2017)
Background. Portfolios are increasingly used across a range of disciplines in health professional education to support reflective practice and to help assess studentsâ€™ academic and professional development. However, their value in postgraduate education is uncertain.Objectives. To identify the role of portfolios in the development and assessment of professional competencies in postgraduate maternal and child public health education.Methods. A qualitative retrospective review of 35 student portfolios was conducted. Thematic content analysis of portfolios was done, identifying emerging themes and analysing patterns.Results. Two major themes were explored â€" the benefit of the portfolio to the student and to faculty. For students, portfolios promoted reflective abilities and critical thinking and assisted them in planning learning needs. For faculty, the portfolios assisted in monitoring studentsâ€™ growth over time, identified learning gaps, helped to establish if expected learning outcomes were being attained and provided feedback on studentsâ€™ application of academic learning to professional practice. Portfolios also offered students an opportunity to provide critical feedback on curricula content and course pedagogic activities.Conclusion. Portfolios are an under-utilised assessment and self-development tool in postgraduate training. They allow students to self-assess their attainment of personal learning needs, professional growth and competency achievement and provide faculty with useful feedback on curriculum content, educational activities and competency attainment.